KETRANSITIFAN TEKS BERITA PUNGUTAN LIAR DI SEKOLAH MELALUI MEDIA DARING (Transitivity of News Text regarding Illegal Retribution at Schools through Online Media) - Nurlina Arisnawati (SAWERIGADING, 2020)
Corruption is a big problem in Indonesia, and it is always reporting on media. One of them is illegal retribution in school. This research discusses the transitivity of news text regarding the wild levy at school. The aim is to describe the meaning of the material process through the verb of  transitivity in reporting illegal retribution at school. The method used is a descriptive- qualitative method with a critical discourse analysis approach by Norman Fairclough. Data on this research are transitive sentences, and the source of the data is the news text of illegal retribution at school, which takes from the online media of beritakotamakassar. fajar.co.id., and makassar.tribunnews.com with ten titles of news regarding the wild retribution at school published in March 2017. The results of this research indicate that in terms of transitivity, online media (beritakotamakassar.fajar.co.id and makassar.tribunnews.com) use meaningful material processes of actions, circumstances, events, and mental processes (behaviors) in reporting case of the illegal retribution at school. This transitivity reveals that these two online media use more active verbs rather than passive verbs, which indicate that media are more likely to mention actors rather than to hide subjects, in particular on the dominant actor or subject. Dominant subjects are shown or highlighted by using active verbs, while dominated actors are displayed using passive verbs. The more dominant active verb used is the active verb, which states the meaning of action. It indicates that both media strongly support the steps or actions taken by Law Institutions (Kejari) in handling cases of illegal retribution in school.AbstrakKorupsi merupakan masalah besar di Indonesia sehingga tiada hari tanpa pemberitaannya di media. Salah satunya adalah pungutan liar (pungli) di sekolah. Tulisan ini membahas ketransitifan teks berita pungli di sekolah. Tujuannya adalah mendeskripsikan makna proses material melalui verba ketransitifan dalam pemberitaan pungli di sekolah. Metode yang digunakan adalah metode deskriptif kualitatif dengan pendekatan analisis wacana kritis model Norman Fairclough. Data dalam penelitian ini berupa kalimat transitif, dan sumber datanya adalah teks berita pungli di sekolah yang diambil dari media daring beritakotamakassar.fajar.co.id., dan makassar.tribunnews.com dengan sepuluh judul berita tentang pungli di sekolah yang terbit pada bulan Maret 2017. Hasil penelitian ini menunjukkan bahwa dari segi ketransitifan, media daring (beritakotamakassar.fajar.co.id dan Makassar.tribunnews.com) menggunakan proses material bermakna perbuatan, keadaan, peristiwa dan proses mental (perilaku) dalam memberitakan kasus pungli di sekolah. Ketransitifan ini mengungkapkan bahwa kedua media daring ini lebih banyak menggunakan verba aktif daripada verba pasif yang menandakan bahwa media tersebut lebih cenderung menyebutkan aktor (subjek) daripada menyembunyikan subyek,